Recent Dasycladales (Chlorophyta) in Okinawa Jima in the Central Ryukyus, southwestern Japan: Paleontological implications. (21st March 2017) - Ohba, Hideo; Matsuda, Shinya; Asami, Ryuji; Iryu, Yasufumi
Abstract: Recent dasycladalean algae (Dasycladales, Chlorophyta) are classified into two families, 11 genera, and 44 species, and inhabit the tropical to warm‐temperate waters of the world. Twelve species of dasycladalean algae occur in Okinawa Jima, Ryukyu Islands. In this paper, the present‐day dasycladalean species and their distributions in Okinawa Jima are reported and their paleontological implications are discussed. Dasycladalean algae grow mainly on coral rubble and rocks, often forming large meadows in calm shallow lagoons. However, Dasycladus vermicularis occurs in deeper waters, at depths of 15–89 m, around Okinawa Jima. Neomeris annulata is found at water depths of 0–30 m. These data throw doubt on the interpretation that the occurrence of dasycladalean algae is linked to warm shallow habitats. Abstract : Twelve species of dasycladalean algae occur in Okinawa Jima and nearby Ryukyu Islands and grow mainly on coral rubble and rocks in the intertidal zone, often forming large meadows in calm shallow lagoons. This abundance is probably related to the limited distribution of corals and coralline algae to below the mean low tide level and the suppression of their growth by sediment and nutrients supplied to the coastal flats. A few dasycladalean species occur in deeper waters, suggesting that the occurrence of dasycladalean algae is not always linked to shallow warm habitats.